(untitled) (Journal Of Educational and Psychological Researches, 2015)
The present study aims at knowing the reasons of the student of secondary school abstention from participation in the theatrical activity, and to know the reasons that resulted in this abstention. In addition to that, the study aims at knowing the differences according to variables (gender, scholastic stage, and major of study). The sample of the study was chosen from the secondary schools in Baghdad in the random manner from Al-Karakh and Al-Rusafa districts of (147) students. The questionnaire was used to collected data. The result showed that all the items are intense, the item of (Students do not know how to use their leisure time) obtained the highest degree of tense followed by the item (The rarity of schools specialized in theatrical arts). The two items that got the same degree of intensity are (The conditions of some students prevent them from practicing some activities) and (the crowdedness in the school day and the curricula). These items represented the most intense reasons in addition to other reasons that make student abstain from participating in theatrical activities, the result also shows: • There are (29) intense reasons behind the student of secondary school abstention from participation in the theatrical activity. • The variable of gender has an effect on the students’ abstention from participation in the theatrical activity, between: • Male and female students of intermediate stage for male. • Male students of secondary school and male student of intermediate stage for male student of intermediate stage. • The students of secondary school (male and female) and intermediate stage students (male and female) for the intermediate stage student. • There are no statistical differences between the scientific major male students and the scientific major female students. • There are no statistical differences between the literary major male students and the literary major female students. • There are no statistical differences between the scientific major students and the literary major students.